PENGARUH MOTIVASI TERHADAP KINERJA TENAGA PEMASARAN (STUDI KASUS PADA AGEN ASURANSI PT. AXA FINANCIAL CABANG SEMARANG) - Ardhian Sasmita; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2017)
This research is about the Influence of Work Motivation on Marketing Performance (Case Study at Insurance Agent PT AXA Semarang). This research is done because there are employee performance problems that are suspected caused by less work motivation, in the form of intrinsic motivation and extrinsic motivation from employees of PT. AXA Semarang. This is based on the non-fulfillment of targets set by the company. The purpose of this study was to determine the effect of intrinsic motivation and extrinsic motivation on employee performance either partially or simultaneously. With the holding of this research it can be taken policy about intrinsic motivation problems, extrinsic motivation and employee performance so that company objectives can be achieved optimally. The type of research used is explanatory research or explanatory research. Population in this research is employees of PT. AXA Semarang as many as 156 people. Sample calculation technique using slovin so that the number of samples to 113 respondents. The technique of determining the sample using Proportional Random Sampling. Data collection method using questionnaires while data analysis techniques used are validity, reliability, test t test, F test, coefficient of determination and regression analysis. Calculations in this study using SPSS for windows. The result of the calculation shows that: (1) intrinsic work motivation have positive and significant effect to employee performance of PT. AXA thus increasing intrinsic work motivation will improve performance and decrease intrinsic work motivation will decrease performance, (2) extrinsic work motivation have positive and significant effect to employee performance of PT. AXA, thereby increasing extrinsic work motivation will improve performance and decrease of extrinsic work motivation will decrease performance, (3) intrinsic work motivation and extrinsic work motivation together have positive and significant influence to employee performance of PT. AXA, thus increasing intrinsic and extrinsic work motivation will improve performance and decrease intrinsic and extrinsic work motivation will degrade performance. Suggestions that can be given are (1) should the company pay attention to the problem of intrinsic work motivation by giving awards, promotion, and development for employees of PT. AXA regularly and continuously, (2) company should pay attention to extrinsic work motivation problem by improving supervision, working conditions, salary, relationship with peers, and security, (3) For other researchers, if you want to do research about performance then use variable Other than the variables contained in this study are intrinsic work motivation and extrinsic work motivation to predict performance. Other variables used to predict performance include leadership, compensation, facilities. Thus research on this performance will be more perfect.